Surface Organo-Iron Chemistry Towards Efficient Reverse Water-Gas Shift Catalysis - Colin Hansen; Dirk Baabe; Marc D. Walter; Christophe Copéret (CHIMIA)
The low-temperature reverse water-gas shift (LT-RWGS) is a critical and energy effective technology for syngas production and the mitigation of anthropogenic carbon emissions. Developing efficient and well-defined catalysts for the LT-RWGS, from which structure-activity relationships can be drawn, is a significant challenge. Herein we describe how the identification of the grafting properties of tetramesityldiiron (Fe2Mes4) helps with designing tailored and highly efficient catalysts of PtFe@SiO2 composition. To that end, a molecular analogue, Fe2Mes3OSi(OtBu)3, was synthesized and characterized by X-ray diffraction, 57Fe-Mössbauer and 1H-NMR spectroscopy. The results confirmed that tetramesityldiiron grafts onto silica via selective displacement of a single mesityl ligand, forming Fe2Mes3@SiO2, while steric hindrance likely prevents secondary interactions with surface siloxide bridges. This work highlights the potential of tetramesityldiiron as a versatile precursor for synthesizing bimetallic MFe@SiO2 systems, enabling the rational development of highly efficient LT-RWGS and CO2 hydrogenation catalysts.